Sequential treatment with monofluorophosphate and zoledronic acid in osteoporotic rats - Brance, María Lorena (2014)
Objective Osteoporosis is the consequence of an imbalance in bone remodeling caused by excessive resorption or inappropriate bone formation. This paper proposes a sequential treatment with monofl uorophosphate (MFP) and zoledronic acid (Z), together with changes in the calcium content in the diet. Method Seven-week-old female Sprague Dawley rats were divided into fi ve groups ( n 21 per group): (1) sham-operated rats (Sham); (2) ovariectomized (OVX) rats fed with a normal calcium diet (OVX); (3) OVX rats fed with a normal calcium diet and treated sequentially with monofl uorophosphate and zoledronic acid (OVX.G1); (4) OVX rats sequentially fed with a low calcium diet and then a high calcium diet, without treatment (OVX.G2); (5): OVX rats fed with a low calcium diet and then a high calcium diet, treated sequentially with monofl uorophosphate and zoledronic acid (OVX.G3). Results After 150 days, the OVX.G3 group showed a similar bone volume to that of the Sham group due to an increase in trabecular number. Dual X-ray absorptiometry bone analysis showed an increase of 9.8% compared with OVX rats. Additionally, an increase in the fracture load at the cortical bone and higher fracture load, ultimate load and stiffness in the compression test were found. Conclusion The sequential treatment with monofl uorophosphate and zoledronic acid increases trabecular bone mass, bone mineral density and bone strength.